2021
DOI: 10.1136/bmjopen-2021-048676
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity in South Africa: a systematic review of prevalence studies

Abstract: ObjectivesTo review prevalence studies of multimorbidity in South Africa to identify prevalence estimates, common disease clusters and factors associated with multimorbidity.DesignSystematic review.SettingSouth Africa (general community and healthcare facilities).Data sourcesArticles were retrieved from electronic databases (PubMed, Web of Science, Scopus, CINAHL, Science Direct and JSTOR).Eligibility criteriaStudies addressing the prevalence of multimorbidity in South Africa were eligible for inclusion. A sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 40 publications
3
37
3
Order By: Relevance
“…Furthermore, South Africa reports high burdens of disease due to tuberculosis (TB), NCDs, injuries, and maternal and child health ( 11 ). A systematic review of multimorbidity in the country ( 12 ) found that multimorbidity is prevalent, especially among women and older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, South Africa reports high burdens of disease due to tuberculosis (TB), NCDs, injuries, and maternal and child health ( 11 ). A systematic review of multimorbidity in the country ( 12 ) found that multimorbidity is prevalent, especially among women and older adults.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review of prevalence studies from South Africa reported a 3%-23% prevalence of multimorbidity in studies with a wide range of age groups and 30%-71% in older adults. 26 The higher prevalence of multimorbidity in the South African sites in the current study (54%-66%) may be attributed to the advanced epidemiological transition and increasing urbanisation in South Africa. 27 This coincides with a higher BMI and prevalence of obesity in the three South African sites compared with the West and East African sites.…”
Section: Discussionmentioning
confidence: 58%
“…Additionally, the inclusion of certain diseases like HIV and tuberculosis seem to be context dependent (Ho et al 2021). Unless the focus is specifically on NCDs, South African studies on multimorbidity often include HIV and tuberculosis because they are both endemic chronic infections (Alaba and Chola 2013;Ataguba 2013;Chang et al 2019;Peltzer 2018;Roomaney et al 2022;Roomaney et al 2021;Sharman and Bachmann 2019;Wade et al 2021;Weimann et al 2016;Wong et al 2021).…”
Section: Measurement Of Multimorbiditymentioning
confidence: 99%
“…This has implications for individuals and health systems worldwide, but particularly in low-and middle-income countries (LMICs), which already face a large burden of NCD-related deaths (Basto-Abreu et al 2022). Existing research on multimorbidity has been highly concentrated in high-income countries (HICs), but the literature on multimorbidity in LMICs is expanding, with several studies recently published (Abebe et al 2020;Chang et al 2019;Kamkuemah et al 2022;Keetile et al 2020;Khorrami et al 2020;Roomaney et al 2021;Sharman and Bachmann 2019). The nature of multimorbidity and its potential risk factors may differ in LMICs compared to HICs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation